Black TiO2 and Oxygen Vacancies: Unraveling the Role in the Thermal Anatase-to-Rutile Transformation - Mattia Allieta; Mauro Coduri; Alberto Naldoni (Applied Nano, 2024)
Understanding the role of oxygen vacancies in the phase transformation of metal oxide nanomaterials is fundamental to design more efficient opto-electronic devices for a variety of applications, including sensing, spintronics, photocatalysis, and photo-electrochemistry. However, the structural mechanisms behind the phase transformation in reducible oxides remain poorly described. Here, we compare P25 and black TiO2 during the thermal anatase-to-rutile transformation using in situ synchrotron powder diffraction. The precise measurement of the phase fractions, unit cell parameters, and Ti-O bond sheds light on the phase transformation dynamics. Notably, we observe distinct temperature-dependent shifts in the relative phase fractions of anatase and rutile in both materials highlighting the role of the oxygen vacancy in promoting the phase transformation. We employ bond valence concepts for structural modeling, revealing unique trends in temperature evolution of Ti-O distances of black rutile, confirming that this TiO2 phase is preferentially reduced over anatase. These findings not only enhance our understanding of phase transitions in TiO2 but also open new ways for the design of advanced photocatalytic materials through targeted phase control.